Biological Efficacy of Ionizing Radiation Sources on 3D Organotypic Tissue Slices Assessed by Fluorescence Microscopy - Shestakova, Victoria; Smirnova, Anna; Yakimova, Anna; Koryakin, Sergey; Baranovskii, Denis; Saburov, Vyacheslav; Yatsenko, Elena; Moiseev, Alexander; Ivanov, Sergey; Smirnova, Ekaterina; Belkina, Svetlana; Demyashkin, Grigory; et al. (Current Radiopharmaceuticals, 2025)
Objective Traditional cell-based radiobiological methods are inadequate for assessing the toxicity of ionizing radiation exposure in relation to the microstructure of the extracellular matrix. Organotypic tissue slices preserve the spatial organization observed in vivo, making the tissue easily accessible for visualization and staining. This study aims to explore the use of fluorescence microscopy of physiologically relevant 3D tissue cultures to assess the effects of ionizing radiation. Methods Organotypic tissue slices were obtained by vibratome, and their mechanical properties were studied. Slices were exposed by two ionizing radiation sources; electron beams (80 Gy and 4 Gy), and soft gamma irradiation (80 Gy and 4 Gy). Two tissue culture protocols were used: the standard (37°C), and hypothermic (30°C) conditions. A qualitative analysis of cell viability in organotypic tissue slices was performed using fluorescent dyes and standard laser confocal microscopy. Results Biological dosimetry is represented by differentially stained 200-μm thick organotypic tissue sections related to living and dead cells and cell metabolic activity. Conclusion Our results underscore the ability of fluorescence laser scanning confocal microscopy to rapidly assess the radiobiological effects of ionizing radiation in vitro on 3D organotypic tissue slices.
Keywords: physiological relevance